Penerapan Bagi Hasil Maro Perspektif Akad Mukhabarah (TAWAZUN: Journal of Sharia Economic Law, 2020)
Mukhabarah is a profit sharing partnership between the land owner and the sharecropper, where the land owner surrenders his land to the sharecropper and the capital is fully borned by the sharecropper. Mukhabarah which are take a place in Brakas Village, people are more familiar with "maro". The profit sharing collaboration was based on verbal agreements based on trust without witnesses and it is not determined how long the collaboration will be. The study aims to analyse what the agricultural system are used, what are the reasons for profit sharing, and how  "maro" system is compatible with the Mukhabarah. The research is used qualitative method with a descriptive approach, data collection methods through observation, interviews, and document review. The results found that smallholders and landowners preferred to profit sharing rather than rent. Furthermore, the implementation of profit sharing cooperation in Brakas Village was a mukhabarah agreement in Islamic law, but in practice was not fully in accordance with the existing Islamic concept, because there were some things that were not appropriate.